Writing caste, writing gender : reading Dalit women's testimonios - Rege, Sharmila (New Delhi : Zubaan, 2013)
Study on the autobiographies of Dalit women from Maharashtra, India.
Includes bibliographical references.
Keywords: Poor women -- India -- Maharashtra -- Biography; Dalits -- India -- Maharashtra -- Biography